Genealogy in the 19th Century: Obligation and Means, Versus Experience and Emotion - Railaitė-Bardė, Agnė (Bibliotheca Lituana, 2019)
Genealogy and genealogical self-awareness were very important elements of the frame of a noble society’s fortress in the 19th century. The analysis of some genealogical trees, schemes, etc. and the diary-memoir of a noble woman Gabrielė Giunterytė-Puzinienė showed several genealogical aspects treasured by nobles. Family members who were high-ranking soldiers, patrons, or belonged to the clergy were treated very respectfully. Having a wide net of family ties and high-status relatives were a remarkable tool for showing ones family’s origin and position in the society. Wealth played an important role as well. Various official and legal documents, individual contemplations, memories and memoirs of other persons or armorials created by Szymon Okolski and Bartosh Paprocki served as remarkable sources for keeping the genealogical memory of families alive. Genealogical trees, schemes etc. could be treated as more reliable sources for genealogical self-awareness because of the elimination of the subjective viewpoint, as we can face it in the abovementioned diary. Nevertheless, the Giedraitis Family case negated this statement. G. Giunterytė-Puzinienė’s diary-memoir is an extraordinary source for exploring genealogical identity. Genealogy is a vivid and detailed story in this book. One can smell, hear, and touch it. Collective holidays, events, and various forms of recreation became tools for strengthening the genealogical self-awareness and family memory.
Keywords: 19th century; affirmation of nobility; genealogical self-awareness; genealogical trees and schemes; Gabrielė Giunterytė-Puzinienė; diary-memoir